ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKTIVITAS KERJA PEGAWAI BALAI TEKNOLOGI KOMUNIKASI DAN PENDIDIKAN DIY - Asteria, Beta (Jurnal Manajemen, 2022)
This study aims to determine how much influence the variables of work motivation, work compensation and work environment have on the work productivity of Balai Tekkomdik DIY employees. This type of research is a quantitative research. The sampling technique used is a saturated sample. All employees are used as samples in this study. SPSS version 22 was used in the analysis of research data. Data analysis using linear regression. T test, F test and R2 test were performed. The results of the study stated that the work motivation variable had a positive and significant effect on employee productivity at Balai Tekkomdik DIY. The work compensation variable does not have a significant effect on the work productivity of Balai Tekkomdik DIY employees. And the Work Environment variable has a positive and significant effect on employee productivity at Balai Tekkomdik DIY. Keywords : Work Motivation, Work Compensation, Work Environtment and Work Productivity